Staying Strong in the Middle: A Literature Review on Sandwich Generation Resilience - Wildah Azmah Azizah; Ratna Dyah Suryaratri; Herdiyan Maulana; Zarina Akbar (International Conference on Psychology and Education (ICPE), 2025)
The sandwich generation phenomenon is commonly observed in developing countries, including Indonesia. This generation is caught between the responsibilities of caring for aging parents and raising children, resulting in dual roles that are susceptible to role conflict. These role conflicts can affect not only personal life but also work and family domains. However, not all individuals experience the same negative impacts, as some are able to adapt positively through resilience. Resilience enables individuals to endure and thrive amid complex role demands. This literature review aims to explore the dynamics of resilience within the context of the sandwich generation and to identify the factors that contribute to enhancing resilience. The method used was a literature review, with a total of 10 articles included based on the screening process. The findings indicate that resilience in the sandwich generation is influenced by both internal and external factors. Moreover, resilience plays a critical role in promoting psychological well-being, improving quality of life, and strengthening individuals' adaptive capacity.